2022
DOI: 10.4314/jcmphc.v34i3.12
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Willingness to Use Modern Contraceptives among female undergraduate students in a tertiary institution in Nigeria: The Health Belief Approach

Abstract: Background: More than half of unintended pregnancies in Nigeria end in induced abortion. Unsafe abortion from unintended pregnancies contributes significantly to maternal mortality in Nigeria. Modern contraceptives have proven useful in preventing unintended pregnancy. The health belief model is a comprehensive tool that can be used to predict contraceptive behaviour. It provides a theoretical framework that gives better understanding of how individual beliefs affect contraceptive behaviour. This study determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Perceived self-efficacy, the only construct in the emotional factor domain, showed a strong significant association with contraceptive use among both groups. Evidence has also corroborated the important role self-efficacy plays in shaping contraception decisions among young people, and indeed the reproductive age population in Nigeria, as young people with higher self-efficacy are more likely to take charge of their sexual health by actively seeking and using contraception [27,28]. Studies from neighboring countries like Ghana also confirmed the association [29].…”
Section: Discussionmentioning
confidence: 79%
“…Perceived self-efficacy, the only construct in the emotional factor domain, showed a strong significant association with contraceptive use among both groups. Evidence has also corroborated the important role self-efficacy plays in shaping contraception decisions among young people, and indeed the reproductive age population in Nigeria, as young people with higher self-efficacy are more likely to take charge of their sexual health by actively seeking and using contraception [27,28]. Studies from neighboring countries like Ghana also confirmed the association [29].…”
Section: Discussionmentioning
confidence: 79%